Lymph Node Metastasis Spread Patterns and the Effectiveness of Prophylactic Neck Irradiation in Sinonasal Squamous Cell Carcinoma (SNSCC) - Liu, Qian; Qu, Yuan; Wang, Kai; Wu, Runye; Zhang, Ye; Huang, Xiaodong; Zhang, Jianghu; Chen, Xuesong; Wang, Jingbo; Xiao, Jianping; Yi, Junlin; Xu, Guozhen; et al. (Frontiers in Oncology, 2022)
Objectives To analyze the incidence and spread of lymph node metastasis (LNM) and the effectiveness of prophylactic neck irradiation in patients with SNSCC. Methods A total of 255 patients with SNSCC were retrospectively reviewed. The LNM spread pattern was revealed. The clinical parameters related to LNM and the prognostic value of elective neck irradiation (ENI) were assessed. Results The initial LNM rate was 20.8%, and the regional recurrence (RR) rate was 7.5%. Lymphatic spreading in SNSCC followed the common trajectories: a. level Ib  level II  level Va/level III/IV lymph nodes (LNs); b. retropharyngeal lymph nodes (RPLNs)  level II LNs. The most frequently involved site was level II LNs (16.1%), followed by level Ib LNs (10.2%), RPLNs (4.7%), level III LNs (3.2%), level Va LNs (1.6%), level IVa LNs (1.4%) and level VIII LNs (0.8%). The median follow-up time was 105 months. The 5-year overall survival (OS) was 55.7% for N0 patients and 38.5% for patients with initial N+ or N- relapse (p = 0.009). ENI (p = 0.013) and absence of nasopharynx involvement (p = 0.026) were associated with a significantly lower RR rate. Conclusions Patients with LNM had poorer survival than those who never experienced LNM. Lymphatic spread in SNSCC followed predictable patterns. ENI effectively reduced the RR rate in patients at high risk.